Analisis Putusan Nomor 2058 K/PDT/2019 Tentang Wanprestasi Perjanjian Jual Beli Rumah - Emir Syarif Fatahillah Pakpahan; Nofrianti Limbong; Citra Bunga Ramadhita (Warmadewa Press, 2025)
Supreme Court Decision Number 2058 K/Pdt/2019 is a case of default arising from a house sale and purchase agreement between a buyer and a seller. In this case, the seller did not fulfill the obligation to hand over the object of the sale and purchase in the form of a house along with a certificate even though the buyer had made the payment according to the agreement. This study aims to analyze the judge's legal considerations in deciding the case of default in a house sale and purchase agreement based on the decision. This study uses a normative legal research method with a statutory approach and decision study.